Instabilité et bifurcation du soufflage de membranes hyperélastiques - Chevaugeon, Nicolas; Marckmann, Gilles; Verron, Erwan; Peseux, Bernard (European Journal of Computational Mechanics, 2002)
This article deals with the post-bifurcating behaviour of inflated hyperelastic membranes. Axisymmetrical and three dimensional formulations are studied. In both cases, the resulting algebraic system is solved by the combining classical Newton-Raphson scheme and the arc-length continuation method. The emphasize is laid on singular points and secondary paths are pointed out. Finally, numerical examples are considered in order to illustrate the developments.